A Study on Risk Assessment in Tunnelling Construction for Klang Valley Mass Rapid Transit (KVMRT) Putrajaya Line - Yaacob, Nurul Ainaa Syuhada; Yahya, Musli Nizam; Samsudin , Noor Aiman; Shoabani, Shahrul Nizam (Progress in Engineering Application and Technology, 2023)
Effective management of risk factors is crucial for the successful implementation of such complex projects. The underground projects in Kuala Lumpur will encounter a range of constraints and challenges in terms of design and construction, which are specific to the city’s geology. This study focuses on the specific risks and challenges associated with tunnelling construction in the KVMRT project. Through a comprehensive literature review, risk factors related to tunnel construction were identified. The Analytic Hierarchy Process (AHP) was employed to analyze potential factors contributing to problems during tunnelling works. Industry experts from the KVMRT project were interviewed using a semi-structured approach to gather data, with a specific focus on the TU3 drive from Hospital Kuala Lumpur Crossover to Ampang Park Station of the MRT Putrajaya Line. The results revealed that ground conditions emerged as the primary factor causing problems in tunnelling construction. A risk register was utilized to identify potential mitigation plans. The study concludes with key findings, recommendations, and conclusions pertaining to the project. The ground condition poses risks such as tunnel collapses, ground subsidence, and water ingress. Thus, future studies should focus on this factor.